TRACKING DAN MONITORING TRUK PENGANGKUT SAMPAH DI DINAS LINGKUNGAN HIDUP KABUPATEN MINAHASA - Daeng, Mushendra; Rompas, Parabelem Tinno Dolf; Santa, Kristofel (Program Studi Teknik Informatika, 2025)
As technology develops in our lives, this results in demands in every aspect, for example in government institutions. In this case, technological developments are in the form of application systems and the web, where the web functions for monitoring and the application functions for tracking, which is useful for assisting office employees in supervising field workers, namely waste transport drivers. The development of this system uses the RAD method which has 4 stages, namely planning, system design, development process and collecting feedback, then implementation, while for developing Android-based applications using the Flutter Framework with the Dart programming language and for the website itself using the Laravel Framework with the PHP programming language. It is hoped that this research can facilitate the monitoring process, reduce errors in the reporting process, and increase the efficiency of the work processes of employees in the Minahasa Regency Environmental Service.